Analisis Keadilan Bagi Terdakwa Tindak Pidana Penganiayaan Dalam Putusan Pengadilan Negeri Labuha Nomor: 38/PID.B/2024/PN LBH - Kobu, Djestylona Kobu; Stomer, Alfandi S.; Buturu, Suwarjono (Jurnal Ilmiah Wahana Pendidikan, 2025)
The type of research used in this writing is normative juridical research. What is meant by juridical research is looking at legal aspects based on statutory regulations, while normative research is research in the field of law to discover legal rules and doctrines. -legal doctrine to answer the legal issues contained in the Labuha District Court Decision in criminal case Number 38/Pid.b/2024/Pn Lbh). Method The approaches used in this research are: Statute Approach and Case Approach. The judge's decision is the product of the trial process in court. Meanwhile, the court is the last place for justice seekers to flee, so the judge's decision should be able to meet the demands of justice seekers. Regarding this, the judge in deciding the case must reflect three elements, namely justice, legal certainty, expediency, however, these three elements, namely justice, legal certainty, expediency, are not reflected in the criminal case decision Number 38/Pid.b/2024/Pn Lbh).